Case‐based intensive veterinary radiology clerkship improves students' radiographic interpretation skills and overall course satisfaction scores. Issue 2 (6th December 2021) - Gallastegui, Aitor; Spoldi, Elisa; Billhymer, Audrey C.; Stefanou, Candice R.
Abstract: The variability in diagnostic imaging caseload, increasing class sizes, high hospital workloads, and the progressive departure of veterinary radiologists from academia can lead to inconsistent and reduced teaching opportunities. This one group pretest, posttest study aimed to compare the learning outcomes of students enrolled in two veterinary radiology clerkship models. Our hypothesis was that the learning and satisfaction scores of students in a case‐based veterinary radiology clerkship would be higher than those in a clinical veterinary radiology clerkship. During the spring and summer semesters of 2019, students were assigned to a clinical (CRC) or case‐based (CBRC) radiology clerkship model, respectively. Prior to starting the clerkship and at the conclusion thereof, all students took identical radiographic interpretation quizzes. Four major areas of learning were assessed: knowledge base (KB), diagnostic test interpretation (DTI), problem prioritization and differential diagnosis (PPDDX), and critical thinking (CrT). A total of 41 of 48 (CRC) and 130 of 151 (CBRC) students enrolled in this study; 15 and 34, respectively, were off‐shore students, while the remainder were in‐house students. In‐house students improved their scores with CRC and CBRC, but achieved better scores in the four areas with CBRC. Off‐shore students only improved their scores with CBRC. In both groups, there was a negative effect of CRC on DTI. Course satisfaction score was 3.21 on CRC and 4.38 on CBRC (range 1‐5). An intensive, case‐based, discussion‐focused veterinary radiology clerkship can improve students' radiographic interpretation skills and overall course satisfaction scores.